Pilatus Dalam Pengakuan Iman Rasuli: Dalam Terang 1 Timotius 6:12-13 - Yonky Karman (Institut Agama Kristen Negeri Toraja, 2021)
Churches and theologians usually interpret the mention of Pilate in the Apostles' Creed as a time frame during the reign of Roman political rulers for the events of Jesus' passion, thereby providing a historical framework for Christ's redemptive work. The phrase “under Pontius Pilate” in the church creed is taken for granted with the same meaning as the Greek phrase epi Pontiou Pilatou in 1 Timothy 6:13, the only direct reference in the New Testament. However, the Bible translation of the Greek phrase is usually “before Pontius Pilate”, slightly different from the creedal formulation. Biblically, there is a connection between epi Pontiou Pilatou and Jesus’ long testimony before Pilate’s trial in the gospel of John, the only gospel that explicitly mentions Jesus coming into the world “to testify to the truth” (John 18:37, NRSV). This article adds a theological significance to that mention in light of I Timothy 6:12-13. Not only Jesus “suffered under Pontius Pilate”, He also gave testimony “before” the Roman administrator, a representation of the then world, and thus the witness of the church throughout the ages before the world.Gereja dan teolog biasanya menafsirkan penyebutan Pilatus dalam Pengakuan Iman Rasuli sebagai kerangka waktu selama pemerintahan penguasa politik Romawi untuk peristiwa sengsara Yesus, demikian memberikan kerangka sejarah untuk karya penebusan Kristus. Frasa “di bawah pemerintahan Pontius Pilatus” dalam kredo gereja diandaikan begitu saja sama maksudnya dengan frasa epi Pontiou Pilatou dalam teks Yunani 1 Timotius 6:13, satu-satunya rujukan langsung dalam Perjanjian Baru. Namun, terjemahan Alkitab untuk frasa Yunani itu biasanya “di muka Pontius Pilatus”, sedikit berbeda dari rumusan kredo. Secara alkitabiah, ada hubungan antara epi Pontiou Pilatou dan kesaksian panjang Yesus di muka pengadilan Pilatus dalam Injil Yohanes, satu-satunya Injil yang secara eksplisit menyebutkan Yesus datang ke dalam dunia “untuk memberi kesaksian tentang kebenaran” (Yoh. 18:37). Artikel ini menambahkan signifikansi teologis untuk penyebutan itu bahwa Yesus tidak hanya “menderita di bawah pemerintahan Pontius Pilatus”, tetapi juga bersaksi “di muka” wali negeri Romawi itu, sebuah representasi dunia waktu itu. Begitu juga kesaksian gereja sepanjang masa di hadapan dunia.